A critical analysis of the Impeachment power of legislature under the Nigerian Constitution - Sani, Abdullahi (2018)
The power of impeachment is created and vested in the Nigerian legislature under the constitution. Why, when and how the power is to be exercised have been provided under the constitution and some laws. However, compliance with the constitutional requirements for the exercise of this power has always been are concern as almost all the exercises have been challenged in courts for noncompliance. This study, therefore, provides a critical analysis of the law and practice of impeachment. In this light, it analyzes the constitutional and legal provisions in relation to the roles of the lawmakers, chief judges and members of investigation panels. The data used in this study were collected using the library approach and semi-structured interviews conducted with relevant stakeholders. The study found, among others, that noncompliance with the constitutional requirements for impeachment is attributable to some provisions which are difficult to comply with like personal service requirement. Furthermore, the constitution vests enormous impeachment powers on the legislature without any mechanism for check and balance in the course of its exercise. It is also found that there are no provisions on standard of proof of the grounds for impeachment. On judicial review of impeachment, it is found that it is bedeviled by challenges such as delay and lack of respect for court order. Consequently, it is recommended, among others, that the constitution be amended to provide for substituted service where personal service is difficult. Furthermore, Constitutional Court be established and vested with specific power to check the exercise of impeachment power. Standard of proof "on balance of probability" be provided for proof of grounds for impeachment. On the challenges to judicial review of impeachment, it is recommended that time frame to conclude judicial review of impeachment be provided and the laws on contempt proceedings be enforced to ensure compliance with court orders.